Labour and the environment: a natural synergy (Geneva, 2007)
"This publication presents examples of the application of technical expertise, of workplace participation, and of tools that promote workers health and safety problems that extend beyond the workplace into areas such as environmental protection, public health and accountability of employers. It focuses on crucial issues ranging from climate change and energy, chemicals management, and corporate social responsibility and accoutability to future involvement of workers and trade unions with the environment and with efforts to move towards sustainability."